Analisis Peran Badan Wakaf Indonesia (BWI) dalam Pembinaan Nazir Wakaf di Kota Binjai - Syerli Zahara Klara Larasati Br Manalu; Muhammad Nur Iqbal (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
This study aims to analyze the role of the Indonesian Waqf Board (Badan Wakaf Indonesia/BWI) in supervising, fostering, and developing waqf management in Indonesia, as well as identifying the challenges faced in the development of productive waqf. The research employs a qualitative method with a library research and interview approach. The findings indicate that BWI plays a significant role in enhancing the professionalism of waqf managers (nazhir), promoting productive waqf, and strengthening national waqf governance. However, several challenges remain, including limited funding, low public literacy regarding waqf, inadequate capacity of nazhir, and legal issues related to waqf assets. Therefore, stronger government support, capacity building for nazhir, and public education are needed to optimize productive and sustainable waqf management.